Noncommutative fluid dynamics in the Snyder space-time - Abdalla, M. C.B. [UNESP]; Holender, L.; Santos, M. A.; Vancea, I. V. (American Physical Society (APS), 2012)
In this paper, we construct for the first time the noncommutative fluid with the deformed Poincaré invariance. To this end, the realization formalism of the noncommutative spaces is employed and the results are particularized to the Snyder space. The noncommutative fluid generalizes the fluid model in the action functional formulation to the noncommutative space. The fluid equations of motion and the conserved energy-momentum tensor are obtained. © 2012 American Physical Society.